A Wonderful Old World and New Factors of Development - V. A. Shamakhova; N. M. Mezhevich (Евразийская интеграция: экономика, право, политика, 2021)
The very complex trends in global development are now being reinterpreted. The epidemic and pandemic were accelerating current trends in world development, both obviously negative and conditionally positive. However, there is no new quality of international relations, including international foreign economic relations. Inevitably, traditional contradictions between organizations, countries, classes and social groups are exacerbated.